Polysilicon adsorbent and methods of making and regenerating the same
Patent Information
- Application Number
- CN202611001107.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-07
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-07-07
AI Technical Summary
吸附柱内吸附剂(传统多为活性炭)饱和后,需通过再生工艺恢复活性,现有再生技术普遍采用“电加热+氢气反吹”的方式,存在诸多技术缺陷,且叠加吸附剂水解堵塞问题,导致再生效果差、能耗高、吸附剂寿命短,具体如下:
(1)通过对吸附剂进行精准改性,实现吸附剂表面亲水基团的钝化和疏水修饰,从源头减少氯硅烷水解的活性位点,同时结合铜组分的催化协同效应,快速转化少量的水解中间产物,形成双重抑水解防护,显著抑制了氯硅烷水解反应发生的倾向;
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of polycrystalline silicon production technology, specifically to a polycrystalline silicon adsorbent and its preparation and regeneration methods. Background Technology
[0002] In the polysilicon production process, the adsorption column is the core equipment for removing boron, phosphorus impurities, and trace amounts of chlorosilanes from the circulating hydrogen feed gas. Its adsorption performance directly determines the purity of the polysilicon product. After the adsorbent (traditionally mostly activated carbon) in the adsorption column becomes saturated, it needs to be regenerated to restore its activity. Current regeneration technologies generally employ an "electric heating + hydrogen backflushing" method, which has many technical drawbacks and, coupled with the problem of adsorbent hydrolysis and clogging, results in poor regeneration efficiency, high energy consumption, and short adsorbent lifespan, as detailed below: First, the regeneration of the adsorption column using electric heating involves multiple energy conversion steps and significant heat loss, resulting in an overall energy utilization rate of only about 60%. A large amount of electrical energy is lost through heat dissipation, leading to persistently high power consumption in the regeneration process. Furthermore, the independent operation of electric heating makes it difficult to couple with waste heat from the production system, resulting in low overall energy utilization. Second, adsorbent regeneration is incomplete and has a short lifespan: traditional adsorbents (such as ordinary activated carbon) have low adsorption capacity, poor selectivity for impurities, and poor adaptability to regeneration temperatures. More importantly, existing adsorbents do not specifically modify the activated carbon surface, leaving numerous oxygen-containing hydrophilic groups (-OH, -COOH). These hydrophilic groups are the core active sites for the hydrolysis of chlorosilanes. Upon contact with trace amounts of moisture in the feed gas, they easily trigger the hydrolysis of adsorbed chlorosilanes, generating Si-OH compounds (silanol groups) and amorphous silica gel (SiO2). These hydrolysis products clog the microporous structure of the activated carbon, covering the active adsorption sites. Existing regeneration processes cannot effectively remove these products, severely impacting impurity adsorption and reducing the purity of the recovered hydrogen.
[0003] To address the shortcomings of the existing technologies, there is an urgent need to develop a new process that can achieve efficient adsorption of impurities, solve the core problem of hydrolysis of microsilica on the surface of the adsorbent and the difficulty in removing hydrolysis products, while also realizing energy recovery and utilization, reducing production and operating costs, and meeting the needs of industrial safety production. Summary of the Invention
[0004] The purpose of this invention is to overcome the problems existing in the prior art and provide a polycrystalline silicon adsorbent, its preparation method, and its regeneration method. This polycrystalline silicon adsorbent and regeneration method can suppress the tendency of chlorosilane hydrolysis reactions at the source, while effectively removing trace amounts of hydrolysis products from the adsorbent surface. Furthermore, by combining the economical heat source replacement and comprehensive utilization of waste heat during the regeneration process, it achieves efficient regeneration and energy saving of the reduction tail gas adsorption column.
[0005] To achieve the above objectives, the present invention provides a method for preparing a polycrystalline silicon adsorbent, the method comprising: (1) The adsorbent carrier is subjected to a first purging treatment with dry hydrogen and a second purging treatment with organosilicon vapor diluted with dry hydrogen to obtain the adsorbent precursor. (2) The adsorbent precursor is impregnated in an impregnation solution containing copper salt to obtain a polycrystalline silicon adsorbent.
[0006] A second aspect of the present invention provides a polycrystalline silicon adsorbent prepared by the above method.
[0007] A third aspect of the present invention provides a method for regenerating a polycrystalline silicon adsorbent, the method comprising: (1) The polycrystalline silicon adsorbent was purged with dry hydrogen in the first stage; (2) The polycrystalline silicon adsorbent after step (1) is subjected to a first preheating treatment, and then subjected to a second stage purging treatment with regenerated hydrogen that has undergone a second preheating treatment. (3) The polycrystalline silicon adsorbent after step (2) is subjected to a third-stage purging treatment using regenerated hydrogen that has undergone a second preheating treatment; The polycrystalline silicon adsorbent is the polycrystalline silicon adsorbent provided in the second aspect above.
[0008] This invention overcomes the problems of poor adsorption effect, incomplete regeneration, and high regeneration energy consumption in existing technologies by synergistically modifying the adsorbent and regenerating it. Specifically, it inhibits the hydrolysis of chlorosilanes through precise modification of the adsorbent and combines it with energy-saving regeneration technology and waste heat recovery. It has the following significant beneficial effects: (1) By precisely modifying the adsorbent, the hydrophilic groups on the surface of the adsorbent are passivated and hydrophobically modified, reducing the active sites of chlorosilane hydrolysis from the source. At the same time, combined with the catalytic synergistic effect of the copper component, a small amount of hydrolysis intermediate products are rapidly converted, forming a double hydrolysis inhibition protection, which significantly inhibits the tendency of chlorosilane hydrolysis reaction. (2) By designing the adsorbent regeneration process, the regeneration energy consumption is significantly reduced, the overall thermal efficiency is increased from 60% to over 90%, and the energy is utilized in stages. Compared with the traditional regeneration process, the energy consumption of the regeneration process of this invention is reduced by more than 30%, which significantly reduces the operating cost of polysilicon production. (3) The polycrystalline silicon adsorbent modified by the method of the present invention has an adsorption capacity increased by more than 30%, and its adsorption selectivity for impurities such as chlorosilane, boron, and phosphorus is significantly enhanced. In the regeneration process, high-temperature regeneration and deep regeneration work together to achieve complete desorption of conventional impurities. At the same time, through high-temperature catalytic reaction and gas purging, a small amount of residual microsilicides are completely removed. The performance recovery rate of the regenerated adsorbent can reach more than 95%, ensuring the long-term stable operation of the adsorption column. (4) The adsorbent and its regeneration method of the present invention have excellent process synergy, are suitable for industrial production, and do not require complex equipment. They can be implemented directly on the basis of existing polycrystalline silicon adsorption columns, with controllable costs. At the same time, the good energy consumption control can meet the needs of large-scale, continuous and energy-saving production of polycrystalline silicon, and is easy to promote and apply. Detailed Implementation
[0009] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0010] This invention provides a method for preparing a polycrystalline silicon adsorbent, the method comprising: (1) The adsorbent carrier is subjected to a first purging treatment with dry hydrogen and a second purging treatment with organosilicon vapor diluted with dry hydrogen to obtain the adsorbent precursor. (2) The adsorbent precursor is impregnated in an impregnation solution containing copper salt to obtain a polycrystalline silicon adsorbent.
[0011] This invention focuses on modifying the adsorbent to "inhibit the occurrence of chlorosilane hydrolysis, adapt to regeneration process parameters, and improve regeneration stability." By deeply modifying the adsorbent surface and combining it with the introduction of copper components for synergistic modification, the adsorbent surface is passivated, hydrophobic modified, and catalytic components are loaded. This reduces the active sites for chlorosilane hydrolysis at the source, prevents the triggering of hydrolysis reactions, and improves adsorption performance and adaptability to the regeneration temperature range, ensuring that the modified adsorbent can stably adapt to the entire process of subsequent regeneration.
[0012] According to the present invention, a good adsorption carrier should have a suitable micropore size, thereby having a higher adsorption capacity. Furthermore, a suitable micropore size can also accommodate the desorption of impurities and the removal of hydrolysis products during the regeneration process, so as to avoid micropore blockage during the regeneration process. Therefore, in order to obtain a higher adsorption capacity and a better regeneration and recovery effect, the selection of the adsorption carrier can be adjusted. Preferably, the adsorption carrier is selected from one or more of coconut shell activated carbon, fruit shell activated carbon and molecular sieve, and is more preferably coconut shell activated carbon and / or fruit shell activated carbon.
[0013] According to the present invention, the first purging treatment can efficiently remove some easily detachable oxygen-containing hydrophilic groups from the surface of the adsorbent carrier, thereby reducing the active sites for chlorosilane hydrolysis. To achieve a better removal effect on the oxygen-containing hydrophilic groups on the surface of the adsorbent carrier, preferably, the first purging treatment includes: adjusting the temperature of the adsorbent carrier to 150-200°C, and maintaining a temperature of 15-30m... 3 Purging at a flow rate of / h for 2-8 hours. More preferably, the first purging treatment includes: adjusting the temperature of the adsorbent carrier to 170-180℃ (for example, values such as 170℃, 175℃, 178℃, and 180℃, or any range thereof), and purging at a flow rate of 20-25m. 3 / h (for example, it can be 20m) 3 / h、22m 3 / h, 23.7m 3 / h and 25m 3 Purging for 4-6 hours at a flow rate of / h or any range thereof (e.g., 4h, 4.5h, 5h, and 6h or any range thereof).
[0014] According to the present invention, by using dry hydrogen-diluted organosilicon vapor for a second purging treatment, the organosilicon vapor can covalently bond with the trace amounts of hydrophilic groups remaining on the surface of the adsorbent carrier to form inert siloxane bonds (Si-OC), thereby completely passivating the remaining hydrophilic groups and achieving a fundamental transformation of the adsorbent carrier surface from hydrophilic to hydrophobic. In order to achieve a better microenvironment modification effect on the adsorbent carrier surface and eliminate the tendency of chlorosilane hydrolysis reaction, preferably, the volume fraction of organosilicon in the dry hydrogen-diluted organosilicon vapor is 0.5-3%, preferably 1-2%, for example, it can be 1%, 1.2%, 1.5% and 2% and any value between these values.
[0015] Preferably, in the dry hydrogen-diluted organosilicon vapor, the organosilicon is selected from one or more of methyltrimethoxysilane, methyltriethoxysilane, trimethylchlorosilane and ethyltriethoxysilane, and is more preferably methyltrimethoxysilane and / or methyltriethoxysilane.
[0016] Preferably, the second purging treatment includes: adjusting the temperature of the adsorbent carrier to 140-170°C, and purging for 3-7 minutes. 3 Purging for 1-4 hours at a flow rate of / h. More preferably, the second purging treatment includes: adjusting the temperature of the adsorbent carrier to 150-160℃ (for example, values such as 150℃, 152℃, 155℃, and 160℃, or any range thereof), and purging for 4-6m. 3 / h (for example, it can be 4m) 3 / h, 4.5m 3 / h、5m3 / h and 6m 3 Purge for 2-3 hours at a flow rate of / h or any range thereof (e.g., 2h, 2.5h, and 3h or any range thereof).
[0017] In this invention, after obtaining the adsorbent precursor in step (1), the copper active component is loaded onto its surface and within the micropores to achieve a dual-function synergy of "adsorption-catalysis and hydrolysis inhibition". On the one hand, the copper component can significantly improve the adsorption selectivity and adsorption capacity of the adsorbent for impurities such as chlorosilanes, boron, and phosphorus, reducing the residue of impurities in the recovered hydrogen. On the other hand, even if a very small amount of chlorosilanes is still triggered by trace moisture in the raw gas to undergo hydrolysis and generate Si-OH compounds during the adsorption process, the copper component can also act as a catalyst to rapidly catalyze the dehydration reaction of the Si-OH compounds (2Si-OH=Si-O-Si+H2O↑), thereby converting the Si-OH compounds that clog the micropores into inert Si-O-Si silica gel precursors and excluding them from the system.
[0018] According to the present invention, in order to obtain a better impregnation effect and to better load the copper component onto the adsorbent precursor, preferably, the amount of the impregnation solution is 0.7-1.2g relative to 1g of the adsorbent precursor, preferably 0.8-1g, for example, it can be 0.8g, 0.85g, 0.9g and 1g, or any value between these values.
[0019] Preferably, the copper salt content in the impregnation solution is 10-40 wt%, more preferably 15-30 wt%, for example, it can be 15 wt%, 20 wt%, 24 wt%, and 30 wt%, or any value between these values.
[0020] According to the present invention, the copper salt can be selected from a wide range. In order to facilitate the impregnation process, the copper salt is preferably selected from one or more of copper chloride, copper nitrate, copper sulfate and copper acetate, and more preferably copper chloride and / or copper nitrate.
[0021] According to the present invention, in order to obtain better adsorption performance and adsorption selectivity, as well as better catalytic effect, the copper content in the polycrystalline silicon adsorbent can be adjusted. Preferably, the copper content in the polycrystalline silicon adsorbent is 1-15 wt%, more preferably 6-10 wt%, for example, it can be 6 wt%, 8 wt%, 9 wt%, and 10 wt%, or any value between these values.
[0022] According to a preferred embodiment of the present invention, the impregnation solution further comprises a nickel salt and an additive, wherein the additive is selected from one or more zinc salts and aluminum salts. Specifically, by introducing a certain amount of nickel component, it can synergistically enhance the adsorption capacity and adsorption selectivity of the polycrystalline silicon adsorbent in conjunction with the copper component; by introducing a certain amount of additive, it can synergistically enhance the catalytic ability for the dehydration reaction of Si-OH compounds in conjunction with the copper component.
[0023] According to the present invention, in order to improve the impregnation process and obtain a polycrystalline silicon adsorbent with better performance, the selection and dosage of nickel salt and additives can be adjusted. Preferably, the nickel salt is selected from one or more of nickel chloride, nickel nitrate, nickel sulfate and nickel acetate, and is more preferably nickel chloride and / or nickel nitrate.
[0024] Preferably, the content of the nickel salt in the impregnation solution is 0.5-10 wt%, more preferably 1-8 wt%, for example, it can be 1.8 wt%, 4 wt%, 6.2 wt%, and 8 wt%, or any value between these values.
[0025] Preferably, the molar ratio of copper to nickel in the polycrystalline silicon adsorbent is 1:0.05-0.5, more preferably 1:0.1-0.3, and can be, for example, 1:0.1, 1:0.15, 1:0.2, 1:0.25 and 1:0.3 and any range between these values.
[0026] Preferably, the zinc salt is selected from one or more of zinc chloride, zinc nitrate, zinc sulfate and zinc acetate, and more preferably zinc chloride and / or zinc nitrate.
[0027] Preferably, the aluminum salt is selected from one or more of aluminum chloride, aluminum nitrate, aluminum sulfate, and aluminum acetate, and is more preferably aluminum chloride and / or aluminum nitrate.
[0028] Preferably, the content of the additive in the impregnation solution is 5-25 wt%, more preferably 7-20 wt%, for example, it can be 7.9 wt%, 12 wt%, 18.5 wt%, and 20 wt%, or any value between these values.
[0029] Preferably, the total content of zinc and / or aluminum in the polycrystalline silicon adsorbent is 0.5-5 wt%, more preferably 1-3 wt%, for example, it can be 1 wt%, 2 wt%, 2.5 wt%, and 3 wt%, or any value between these values.
[0030] According to the present invention, in order to achieve a better loading effect on each component in the impregnation solution, the impregnation treatment time is preferably 8-20h, more preferably 12-16h, for example, it can be 12h, 14h, 15h and 16h and any range between these values.
[0031] According to the present invention, the solvent of the impregnation solution can be water, typically deionized water.
[0032] According to the present invention, after the above impregnation treatment is completed, the product is dried to obtain the polycrystalline silicon adsorbent of the present invention. The drying can be performed using conventional drying methods in the art, such as air drying or drying under an inert gas atmosphere.
[0033] A second aspect of the present invention provides a polycrystalline silicon adsorbent prepared by the above method.
[0034] A third aspect of the present invention provides a method for regenerating a polycrystalline silicon adsorbent, the method comprising: (1) The polycrystalline silicon adsorbent was purged with dry hydrogen in the first stage; (2) The polycrystalline silicon adsorbent after step (1) is subjected to a first preheating treatment, and then subjected to a second stage purging treatment with regenerated hydrogen that has undergone a second preheating treatment. (3) The polycrystalline silicon adsorbent after step (2) is subjected to a third-stage purging treatment using regenerated hydrogen that has undergone a second preheating treatment; The polycrystalline silicon adsorbent is the polycrystalline silicon adsorbent provided in the second aspect above.
[0035] According to the present invention, residual hydrogen and light impurities can be removed by subjecting the polycrystalline silicon adsorbent to a first-stage purging treatment, thus completing the preparation before regeneration. To obtain a better purging effect, preferably, the first-stage purging treatment includes: adjusting the temperature of the polycrystalline silicon adsorbent to 10-40°C, and maintaining a temperature of 10-40m... 3 Purging at a flow rate of / h for 10-80 min. More preferably, the first stage of purging treatment includes: adjusting the temperature of the polycrystalline silicon adsorbent to 20-30℃ (for example, values such as 20℃, 25℃, 28℃, and 30℃, or any range between these values), and purging for 20-30 min. 3 / h (for example, it can be 20m) 3 / h、22m 3 / h, 25m 3 / h and 30m 3 Purge for 30-60 minutes at a flow rate of (e.g., 30 min, 40 min, 50 min, and 60 min, or any range thereof).
[0036] According to the present invention, by preheating the polycrystalline silicon adsorbent after the first stage purging treatment and introducing preheated regenerated hydrogen for the second stage purging treatment, the weak adsorbed species on the surface of the polycrystalline silicon adsorbent can be removed, and high-temperature regeneration can be completed. In order to obtain a better desorption and regeneration effect, preferably, the temperature of the polycrystalline silicon adsorbent in the first preheating treatment is 110-150°C, preferably 120-140°C, for example, it can be 120°C, 130°C, 135°C and 140°C and any range between these values.
[0037] Preferably, the second preheating treatment makes the temperature of the regenerated hydrogen 90-130°C, more preferably 100-120°C, for example, it can be 100°C, 105°C, 110°C and 120°C and any range between these values.
[0038] Preferably, the second stage purging treatment includes: heating the polycrystalline silicon adsorbent to 130-170°C at a heating rate of 0.5-3°C / min, and then purging at a temperature of 20-60m. 3 Purging at a flow rate of / h and a pressure of 0.05-0.2 MPa for 0.5-5 h. More preferably, the second stage purging treatment includes: heating the polycrystalline silicon adsorbent to 140-160℃ (e.g., values such as 1℃ / min, 1.5℃ / min, 1.8℃ / min, and 2℃ / min, and any range thereof) at a heating rate of 1-2℃ / min, and then purging at a temperature of 30-50 m. 3 / h (for example, it can be 30m) 3 / h, 40m 3 / h, 45m 3 / h and 50m 3 The process involves purging at a flow rate of 0.08-0.15 MPa (e.g., 0.08 MPa, 0.1 MPa, 0.12 MPa, and 0.15 MPa, or any other value within this range) for 1-3 hours (e.g., 1 hour, 2 hours, 2.5 hours, and 3 hours, or any other value within this range) in the second stage of purging. In this second stage, the initial temperature of the polycrystalline silicon adsorbent during heating is the same as the temperature of the polycrystalline silicon adsorbent after the first preheating treatment. By adjusting the appropriate heating rate and pressure, a more stable and superior desorption and regeneration effect can be obtained.
[0039] According to the present invention, by subjecting the polycrystalline silicon adsorbent, which has undergone high-temperature regeneration after the second-stage purging treatment, to a third-stage purging treatment for deep regeneration, the synergistic effect of the catalytic components contained within the polycrystalline silicon adsorbent and the higher-temperature purging process can be utilized to effectively remove the small amount of Si-OH compounds generated within the polycrystalline silicon adsorbent and the trace amounts of Si-O-Si silica gel precursor obtained from catalytic conversion. This significantly improves the regeneration effect and achieves an extremely high adsorption performance recovery rate. To obtain a regenerated adsorbent with even better performance, preferably, the third-stage purging treatment includes: heating the polycrystalline silicon adsorbent to 150-190°C at a heating rate of 0.5-3°C / min, and then... 3 Purging at a flow rate of / h for 1-8 hours. More preferably, the third-stage purging treatment includes: heating the polycrystalline silicon adsorbent to 160-180℃ (e.g., values such as 1℃ / min, 1.5℃ / min, 1.8℃ / min, and 2℃ / min, or any value between these values) at a heating rate of 1-2℃ / min, and then purging at a flow rate of 30-50m. 3 / h (for example, it can be 30m) 3 / h, 40m 3 / h, 45m 3 / h and 50m 3 Purging is performed at a flow rate of / h or any range thereof for 3-5 hours (e.g., 3h, 4h, 4.5h, and 5h or any range thereof). In the third stage of purging, the initial temperature of the polycrystalline silicon adsorbent heating process is the same as the temperature of the polycrystalline silicon adsorbent after the second stage of purging. A suitable heating rate can make the regeneration process more stable.
[0040] According to a preferred embodiment of the present invention, the heating method for the first preheating treatment, the second stage purging treatment and the third stage purging treatment is steam heating.
[0041] According to a preferred embodiment of the present invention, the heating method for the second preheating treatment is to heat the gas discharged from the hydrogen compressor.
[0042] This invention achieves cascaded energy utilization by replacing the traditional electric heating method with the aforementioned steam heating method in the regeneration process, utilizing the waste heat of the recovered hydrogen compressor for preheating of regenerated hydrogen, and employing a multi-stage purging process with stepped temperature rise. This greatly improves the overall thermal efficiency of the regeneration process and significantly reduces regeneration energy consumption.
[0043] According to the present invention, after the third stage of purging treatment described above, a cooling purging process is further included. Preferably, the cooling purging process includes: cooling the polycrystalline silicon adsorbent to 10-40°C at a cooling rate of 1-3°C / min, during which regenerated hydrogen at room temperature is used for purging, and the flow rate of the regenerated hydrogen is 2-4 m³ / min. 3 The adjustment rate was reduced to 5-20m / h. 3 / h, after which the regenerated polycrystalline silicon adsorbent is obtained.
[0044] According to the present invention, after the above-mentioned cooling and purging process is completed, the polycrystalline silicon adsorbent can be pressurized with hydrogen and kept under pressure for later use.
[0045] This invention overcomes the problems of poor adsorption effect, incomplete regeneration, and high regeneration energy consumption in the prior art by synergistically modifying the adsorbent and regenerating it. Specifically, it inhibits the hydrolysis of chlorosilane by precisely modifying the adsorbent and combining it with energy-saving regeneration process and waste heat recovery, thus achieving excellent technical results.
[0046] The present invention will be described in detail below through embodiments.
[0047] In the following examples, the apparatus used is conventional in the art, the operations performed are conventional in the art, and the raw materials and reagents used are commercially available.
[0048] Example 1 I. Preparation of Polycrystalline Silicon Adsorbent (1) Adjust the temperature of the coconut shell activated carbon to 180℃, and use dry hydrogen at 21m 3 Purging was performed at a flow rate of / h for 5 hours; then the temperature of the coconut shell activated carbon was adjusted to 153℃, and methyltrimethoxysilane vapor diluted with dry hydrogen (methyltrimethoxysilane volume fraction of 1.5%) was used at a flow rate of 5.3m. 3 After purging at a flow rate of / h for 2.5h, an adsorbent precursor was obtained (the content of hydrophilic groups decreased by 88wt%).
[0049] (2) A certain amount of copper chloride, nickel nitrate, and aluminum nitrate were dissolved in a certain amount of deionized water to obtain an impregnation solution. The adsorbent precursor was immersed in the impregnation solution (the amount of impregnation solution was 1g relative to 1g of adsorbent precursor; the content of copper chloride in the impregnation solution was 17wt%, the content of nickel nitrate was 3.3wt%, and the content of aluminum nitrate was 7.9wt%), and after immersion for 14h, it was dried for later use. The obtained polycrystalline silicon adsorbent contained 8wt% copper, the molar ratio of copper to nickel was 1:0.13, and the content of aluminum was 1wt%.
[0050] II. Regeneration Process of Polycrystalline Silicon Adsorbent After the polycrystalline silicon adsorbent has been used in the adsorption column for a period of time, deactivation is determined based on the phosphine breakthrough concentration in the tail gas. A phosphine removal rate of 20% or lower is considered adsorbent breakthrough, and the polycrystalline silicon adsorbent is then regenerated. The regeneration process is as follows: (1) Turn off the raw material gas, adjust the temperature of the polycrystalline silicon adsorbent to 25°C, and use dry hydrogen at 25m 3 The polycrystalline silicon adsorbent was purged for 45 minutes at a flow rate of / h to remove weakly adsorbed impurities from its surface.
[0051] (2) The polycrystalline silicon adsorbent obtained after step (1) is preheated to 140°C by steam heating; the regenerated hydrogen is preheated to 120°C by heat exchange using high-temperature gas discharged from the recovered hydrogen compressor; the preheated polycrystalline silicon adsorbent is heated from 140°C to 160°C by steam heating at a heating rate of 1°C / min, and the preheated regenerated hydrogen is heated at 50m 3 Purge for 2 hours at a flow rate of / h and a pressure of 0.09MPa.
[0052] (3) The polycrystalline silicon adsorbent obtained after step (2) is heated with steam at a heating rate of 1℃ / min from 160℃ to 180℃, and preheated regenerated hydrogen is used in a 50m... 3 Purge at a flow rate of / h for 5 hours until the impurities in the exhaust gas are ≤0.05ppb and the moisture content is ≤0.1ppm.
[0053] (4) After the purging in step (3), the polycrystalline silicon adsorbent is cooled to 25°C at a cooling rate of 1°C / min. During the cooling process, room temperature regenerated hydrogen is continuously used for purging, with a regenerated hydrogen flow rate of 3m³ / min. 3 The adjustment rate is from 50m / h 3 / h dropped to 15m 3 / h, after which the regenerated polycrystalline silicon adsorbent is obtained. The regenerated polycrystalline silicon adsorbent is pressurized with hydrogen gas and kept under pressure for later use.
[0054] Example 2 I. Preparation of Polycrystalline Silicon Adsorbent (1) Adjust the temperature of the fruit shell activated carbon to 170℃, and use dry hydrogen at 24m 3 Purging at a flow rate of / h for 4 hours; then adjusting the temperature of the coconut shell activated carbon to 155℃, and purging with methyltrimethoxysilane vapor diluted with dry hydrogen (methyltrimethoxysilane volume fraction of 2%) at a flow rate of 5m 3 After purging at a flow rate of / h for 3h, an adsorbent precursor was obtained (the content of hydrophilic groups decreased by 90wt%).
[0055] (2) A certain amount of copper nitrate, nickel chloride, and zinc nitrate were dissolved in a certain amount of deionized water to obtain an impregnation solution. The adsorbent precursor was immersed in the impregnation solution (the amount of impregnation solution was 1g relative to 1g of adsorbent precursor; the content of copper nitrate in the impregnation solution was 29.5wt%, the content of nickel chloride was 6.2wt%, and the content of zinc nitrate was 8.69wt%), and after immersion for 12h, it was dried for later use. The obtained polycrystalline silicon adsorbent contained 10wt% copper, the molar ratio of copper to nickel was 1:0.3, and the content of zinc was 3wt%.
[0056] II. Regeneration Process of Polycrystalline Silicon Adsorbent After the polycrystalline silicon adsorbent has been used in the adsorption column for a period of time, deactivation is determined based on the phosphine breakthrough concentration in the tail gas. A phosphine removal rate of 20% or lower is considered adsorbent breakthrough, and the polycrystalline silicon adsorbent is then regenerated. The regeneration process is as follows: (1) Turn off the raw material gas, adjust the temperature of the polycrystalline silicon adsorbent to 30°C, and use dry hydrogen at 20m 3 Purging at a flow rate of / h for 30 minutes is used to remove weakly adsorbed impurities from the surface of the polycrystalline silicon adsorbent.
[0057] (2) The polycrystalline silicon adsorbent obtained after step (1) is preheated to 130°C by steam heating; the regenerated hydrogen is preheated to 110°C by heat exchange using high-temperature gas discharged from the recovered hydrogen compressor; the preheated polycrystalline silicon adsorbent is heated from 130°C to 150°C by steam heating at a heating rate of 1.5°C / min, and the preheated regenerated hydrogen is heated at 40m 3 Purge for 3 hours at a flow rate of / h and a pressure of 0.085MPa.
[0058] (3) The polycrystalline silicon adsorbent obtained after step (2) is heated with steam at a heating rate of 2℃ / min from 150℃ to 180℃, and preheated regenerated hydrogen is used in a 50m... 3 Purge at a flow rate of / h for 3 hours until the impurities in the exhaust gas are ≤0.05ppb and the moisture content is ≤0.1ppm.
[0059] (4) After the purging in step (3) is completed, the polycrystalline silicon adsorbent is cooled to 25°C at a cooling rate of 2°C / min. During the cooling process, room temperature regenerated hydrogen is continuously used for purging, and the flow rate of the regenerated hydrogen is 4m³ / min. 3 The adjustment rate is from 50m / h 3 / h dropped to 10m 3 / h, after which the regenerated polycrystalline silicon adsorbent is obtained. The regenerated polycrystalline silicon adsorbent is pressurized with hydrogen gas and kept under pressure for later use.
[0060] Example 3 I. Preparation of Polycrystalline Silicon Adsorbent (1) Adjust the temperature of coconut shell activated carbon to 175℃, and use dry hydrogen at 22m 3 Purging at a flow rate of / h for 6 hours; then adjusting the temperature of the coconut shell activated carbon to 160℃, and purging with methyltriethoxysilane vapor diluted with dry hydrogen (methyltriethoxysilane volume fraction of 1%) at a flow rate of 6m 3 After purging at a flow rate of / h for 2h, an adsorbent precursor was obtained (the content of hydrophilic groups decreased by 91wt%).
[0061] (2) A certain amount of copper chloride, nickel chloride, and aluminum chloride were dissolved in a certain amount of deionized water to obtain an impregnation solution. The adsorbent precursor was immersed in the impregnation solution (the amount of impregnation solution was 0.8g relative to 1g of adsorbent precursor; the content of copper chloride in the impregnation solution was 18.5wt%, the content of nickel chloride was 1.78wt%, and the content of aluminum chloride was 18.5wt%), and after immersion for 16h, it was dried for later use. The obtained polycrystalline silicon adsorbent contained 7wt% copper, the molar ratio of copper to nickel was 1:0.1, and the content of aluminum was 3wt%.
[0062] II. Regeneration Process of Polycrystalline Silicon Adsorbent After the polycrystalline silicon adsorbent has been used in the adsorption column for a period of time, deactivation is determined based on the phosphine breakthrough concentration in the tail gas. A phosphine removal rate of 20% or lower is considered adsorbent breakthrough, and the polycrystalline silicon adsorbent is then regenerated. The regeneration process is as follows: (1) Turn off the raw material gas, adjust the temperature of the polycrystalline silicon adsorbent to 30°C, and use dry hydrogen at 30m 3 Purging at a flow rate of / h for 60 minutes is used to remove weakly adsorbed impurities from the surface of the polycrystalline silicon adsorbent.
[0063] (2) The polycrystalline silicon adsorbent obtained after step (1) is preheated to 120°C by steam heating; the regenerated hydrogen is preheated to 100°C by heat exchange using high-temperature gas discharged from the hydrogen recovery compressor; the preheated polycrystalline silicon adsorbent is heated from 120°C to 140°C by steam heating at a heating rate of 2°C / min, and the preheated regenerated hydrogen is heated at 30m 3 Purge for 1 hour at a flow rate of / h and a pressure of 0.08MPa.
[0064] (3) The polycrystalline silicon adsorbent obtained after step (2) is heated with steam at a heating rate of 1℃ / min from 140℃ to 170℃, and preheated regenerated hydrogen is used at a temperature of 40m. 3 Purge at a flow rate of / h for 5 hours until the impurities in the exhaust gas are ≤0.05ppb and the moisture content is ≤0.1ppm.
[0065] (4) After the purging in step (3) is completed, the polycrystalline silicon adsorbent is cooled to 25°C at a cooling rate of 1°C / min. During the cooling process, room temperature regenerated hydrogen is continuously used for purging, and the flow rate of the regenerated hydrogen is 2m³ / min.3 The adjustment rate is from 40m / h 3 / h decreased to 20m 3 / h, after which the regenerated polycrystalline silicon adsorbent is obtained. The regenerated polycrystalline silicon adsorbent is pressurized with hydrogen gas and kept under pressure for later use.
[0066] Example 4 According to the method of Example 1, the difference is that in the preparation of polycrystalline silicon adsorbent, in step (2), the content of copper chloride in the impregnation solution is 8.5wt%, and the copper content in the obtained polycrystalline silicon adsorbent is 4wt%.
[0067] Example 5 According to the method of Example 1, the difference is that in the preparation of polycrystalline silicon adsorbent, in step (2), the content of copper chloride in the impregnation solution is 27.5 wt%, and the copper content in the obtained polycrystalline silicon adsorbent is 13 wt%.
[0068] Example 6 The method is the same as in Example 1, except that nickel nitrate was not used in step (2) of the preparation of the polycrystalline silicon adsorbent.
[0069] Example 7 The method is the same as in Example 1, except that aluminum nitrate was not used in step (2) of the preparation of the polycrystalline silicon adsorbent.
[0070] Example 8 The method of Example 1 differs in that, in the preparation of the polycrystalline silicon adsorbent, the volume fraction of methylsilane in the methylsilane vapor diluted with dry hydrogen in step (1) is 0.5%.
[0071] Example 9 The method of Example 1 differs in that, in the preparation of the polycrystalline silicon adsorbent, the volume fraction of methylsilane in the methylsilane vapor diluted with dry hydrogen in step (1) is 3%.
[0072] Example 10 The method of Example 1 differs in that, in the preparation of the polycrystalline silicon adsorbent, coconut shell activated carbon is replaced with molecular sieve in step (1).
[0073] Example 11 The method is the same as in Example 1, except that in the preparation of the polycrystalline silicon adsorbent, the temperature of purging the coconut shell activated carbon with dry hydrogen in step (1) is 200°C and the flow rate is 16 m³ / s. 3 / h, the time is 2h.
[0074] Example 12 The method is the same as in Example 1, except that in the preparation of the polycrystalline silicon adsorbent, the temperature at which the coconut shell activated carbon is purged with dry hydrogen in step (1) is 150°C and the flow rate is 18 m³ / s. 3 / h, the time is 8h.
[0075] Example 13 The method is the same as in Example 1, except that in the preparation of the polycrystalline silicon adsorbent, the temperature at which the coconut shell activated carbon is purged with methylsilane vapor diluted with dry hydrogen in step (1) is 140°C and the flow rate is 6.5 m³ / s. 3 / h, the time is 1h.
[0076] Example 14 The method is the same as in Example 1, except that in the preparation of the polycrystalline silicon adsorbent, the temperature at which the coconut shell activated carbon is purged with methylsilane vapor diluted with dry hydrogen in step (1) is 165°C and the flow rate is 3 m³ / s. 3 / h, the time is 4h.
[0077] Example 15 The method is the same as in Example 1, except that in the regeneration process of the polycrystalline silicon adsorbent, in step (2), the polycrystalline silicon adsorbent is heated with steam at a heating rate of 3°C / min from 140°C to 170°C, and preheated regeneration hydrogen is used at a temperature of 20m. 3 Purge for 5 hours at a flow rate of / h and a pressure of 0.05MPa.
[0078] Example 16 The method is the same as in Example 1, except that in the regeneration process of the polycrystalline silicon adsorbent, in step (2), the polycrystalline silicon adsorbent is heated with steam at a heating rate of 0.5℃ / min from 140℃ to 160℃, and preheated regeneration hydrogen is used at 60m 3 Purge for 0.5 hours at a flow rate of / h and a pressure of 0.2MPa.
[0079] Example 17 The method is the same as in Example 1, except that in the regeneration process of the polycrystalline silicon adsorbent, in step (3), the polycrystalline silicon adsorbent is heated with steam at a heating rate of 0.5℃ / min from 160℃ to 190℃, and preheated regeneration hydrogen is used at 60m 3 Purge for 1 hour at a flow rate of / h.
[0080] Example 18 The method is the same as in Example 1, except that in the regeneration process of the polycrystalline silicon adsorbent, in step (3), the polycrystalline silicon adsorbent is heated with steam at a heating rate of 3°C / min from 160°C to 180°C, and preheated regeneration hydrogen is used at a temperature of 20m. 3 Purge for 8 hours at a flow rate of / h.
[0081] Comparative Example 1 According to the method of Example 1, the difference is that in the preparation of polycrystalline silicon adsorbent, in step (1), the coconut shell activated carbon was not purged with methylsilane vapor diluted with dry hydrogen, and the time for purging the coconut shell activated carbon with dry hydrogen was 7.5h.
[0082] Comparative Example 2 The method of Example 1 differs from that step (2) was not performed in the preparation of the polycrystalline silicon adsorbent.
[0083] Comparative Example 3 According to the method of Example 1, the difference is that in the preparation of polycrystalline silicon adsorbent, in step (1), the coconut shell activated carbon was not purged with methylsilane vapor diluted with dry hydrogen, and the time for purging the coconut shell activated carbon with dry hydrogen was 7.5h; at the same time, step (2) was not performed.
[0084] Comparative Example 4 The method of Example 1 differs in that, in the regeneration process of the polycrystalline silicon adsorbent, both dry hydrogen and regenerated hydrogen are replaced with nitrogen.
[0085] Comparative Example 5 The method of Example 1 differs in that, in the regeneration process of polycrystalline silicon adsorbent, the regenerated hydrogen is not preheated in steps (2) and (3).
[0086] Comparative Example 6 The method of Example 1 differs from that step (3) is not performed in the regeneration process of the polycrystalline silicon adsorbent.
[0087] Test Example 1 The regenerated polycrystalline silicon adsorbents obtained in Examples 1-10 and Comparative Examples 1-6 were re-introduced with the reduction tail gas from the low-temperature condensation chlorosilane process. The reduction tail gas flow rate was 30,000 m³ / h. After 8 hours of use, the phosphine content in the adsorption tail gas was measured to evaluate the regeneration effect of the adsorbent. The 8-hour phosphine removal rate was calculated as [(phosphine content in the tail gas before adsorption - phosphine content in the tail gas after 8 hours of adsorption) / (phosphine content in the tail gas before adsorption)] * 100%, where the phosphine content in the tail gas before adsorption was 2 ppba. The test results are shown in Table 1.
[0088] Table 1
[0089] As shown in Table 1, compared to Comparative Examples 1-6, the polycrystalline silicon adsorbents in Examples 1-18 using the technical solution of this invention exhibit better adsorption performance and superior regeneration effect. This invention achieves excellent technical results through specific modification of the polycrystalline silicon adsorbent and the design of corresponding regeneration processes, utilizing the synergistic optimization of both.
[0090] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A method for preparing a polycrystalline silicon adsorbent, characterized in that, The method includes: (1) The adsorbent carrier is subjected to a first purging treatment with dry hydrogen and a second purging treatment with organosilicon vapor diluted with dry hydrogen to obtain the adsorbent precursor. The organosilicon vapor diluted with dry hydrogen has a volume fraction of 1-2%; The first purging treatment includes: adjusting the temperature of the adsorbent carrier to 170-180℃, and maintaining a temperature of 20-25m. 3 Purge for 4-6 hours at a flow rate of / h; The second purging treatment includes: adjusting the temperature of the adsorbent carrier to 150-160℃, and purging at a temperature of 4-6m. 3 Purge for 2-3 hours at a flow rate of / h; (2) The adsorbent precursor is impregnated in an impregnation solution containing copper salt to obtain a polycrystalline silicon adsorbent; The impregnation solution also contains nickel salts and additives, wherein the additives are selected from one or more zinc salts and aluminum salts.
2. The method according to claim 1, wherein, The adsorption carrier is selected from one or more of fruit shell activated carbon and molecular sieves.
3. The method according to claim 1, wherein, The adsorption carrier is selected from coconut shell activated carbon.
4. The method according to any one of claims 1-3, wherein, In the dry hydrogen-diluted organosilicon vapor, the organosilicon is selected from one or more of methyltrimethoxysilane, methyltriethoxysilane, and ethyltriethoxysilane; And / or, relative to 1g of the adsorbent precursor, the amount of the impregnation solution is 0.7-1.2g; And / or, the copper salt is selected from one or more of copper chloride, copper nitrate, copper sulfate, and copper acetate; And / or, the copper salt content in the impregnation solution is 10-40 wt%; And / or, the copper content in the polycrystalline silicon adsorbent is 1-15 wt%; And / or, the impregnation treatment time is 8-20 hours.
5. The method according to claim 4, wherein, In the dry hydrogen-diluted organosilicon vapor, the organosilicon is selected from methyltrimethoxysilane and / or methyltriethoxysilane; And / or, relative to 1g of the adsorbent precursor, the amount of the impregnation solution is 0.8-1g; And / or, the copper salt is selected from copper chloride and / or copper nitrate; And / or, the copper salt content in the impregnation solution is 15-30 wt%; And / or, the copper content in the polycrystalline silicon adsorbent is 6-10 wt%; And / or, the impregnation treatment time is 12-16 hours.
6. The method according to any one of claims 1-3, wherein, The nickel salt is selected from one or more of nickel chloride, nickel nitrate, nickel sulfate, and nickel acetate; And / or, the content of the nickel salt in the impregnation solution is 0.5-10 wt%; And / or, the molar ratio of copper to nickel in the polycrystalline silicon adsorbent is 1:0.05-0.5; And / or, the zinc salt is selected from one or more of zinc chloride, zinc nitrate, zinc sulfate, and zinc acetate; And / or, the aluminum salt is selected from one or more of aluminum chloride, aluminum nitrate, aluminum sulfate, and aluminum acetate; And / or, the content of the auxiliary agent in the impregnation solution is 5-25 wt%; And / or, the total content of zinc and / or aluminum in the polycrystalline silicon adsorbent is 0.5-5 wt%.
7. The method according to claim 6, wherein, The nickel salt is selected from nickel chloride and / or nickel nitrate; And / or, the content of the nickel salt in the impregnation solution is 1-8 wt%; And / or, the molar ratio of copper to nickel in the polycrystalline silicon adsorbent is 1:0.1-0.3; And / or, the zinc salt is selected from zinc chloride and / or zinc nitrate; And / or, the aluminum salt is selected from aluminum chloride and / or aluminum nitrate; And / or, the content of the auxiliary agent in the impregnation solution is 7-20 wt%; And / or, the total content of zinc and / or aluminum in the polycrystalline silicon adsorbent is 1-3 wt%.
8. The polycrystalline silicon adsorbent prepared by the method according to any one of claims 1-7.
9. A method for regenerating a polycrystalline silicon adsorbent, characterized in that, The method includes: (1) The polycrystalline silicon adsorbent was purged with dry hydrogen in the first stage; (2) The polycrystalline silicon adsorbent after step (1) is subjected to a first preheating treatment, and then subjected to a second stage purging treatment with regenerated hydrogen that has undergone a second preheating treatment. (3) The polycrystalline silicon adsorbent after step (2) is subjected to a third-stage purging treatment using regenerated hydrogen that has undergone a second preheating treatment; The polycrystalline silicon adsorbent is the polycrystalline silicon adsorbent as described in claim 8.
10. The method according to claim 9, wherein, The first stage of purging treatment includes: adjusting the temperature of the polycrystalline silicon adsorbent to 10-40°C, and purging at a temperature of 10-40m. 3 Purge for 10-80 minutes at a flow rate of / h; And / or, the first preheating treatment brings the temperature of the polycrystalline silicon adsorbent to 110-150°C; And / or, the second preheating treatment brings the temperature of the regenerated hydrogen to 90-130°C; And / or, the second stage purging treatment includes: heating the polycrystalline silicon adsorbent to 130-170°C at a heating rate of 0.5-3°C / min, and then purging at a temperature of 20-60m. 3 Purge for 0.5-5 hours at a flow rate of / h and a pressure of 0.05-0.2MPa; And / or, the third-stage purging treatment includes: heating the polycrystalline silicon adsorbent to 150-190°C at a heating rate of 0.5-3°C / min, and then purging at a temperature of 20-60m. 3 Purge for 1-8 hours at a flow rate of / h.
11. The method according to claim 10, wherein, The first stage of purging treatment includes: adjusting the temperature of the polycrystalline silicon adsorbent to 20-30°C, and purging at a temperature of 20-30m. 3 Purge for 30-60 minutes at a flow rate of / h; And / or, the first preheating treatment brings the temperature of the polycrystalline silicon adsorbent to 120-140°C; And / or, the second preheating treatment makes the temperature of the regenerated hydrogen 100-120°C; And / or, the second stage purging treatment includes: heating the polycrystalline silicon adsorbent to 140-160°C at a heating rate of 1-2°C / min, and then purging it for 30-50 minutes. 3 Purge for 1-3 hours at a flow rate of / h and a pressure of 0.08-0.15MPa; And / or, the third-stage purging treatment includes: heating the polycrystalline silicon adsorbent to 160-180°C at a heating rate of 1-2°C / min, and then purging it at a temperature of 30-50m. 3 Purge for 3-5 hours at a flow rate of / h.
12. The method according to claim 10, wherein, The heating method for the first preheating treatment, the second stage purging treatment and the third stage purging treatment is steam heating; And / or, the second preheating treatment is performed by heating with high-temperature gas discharged from a hydrogen recovery compressor.
Citation Information
Patent Citations
Functionalized adsorbent and preparation method thereof
CN118616027A
Metal modified adsorbent as well as preparation method and application thereof in circulating hydrogen purification
CN119327420A
Method of preparing high hydrophobic active carbon and its device
CN1903718A